Conceptualising Alkali Pozzolan Cement for Sustainable Future - Kulasuriya, Chandana; Vimonsatit, Vanissorn (Engineers Australia, 2012)
This paper presents the process of a ‘conceptual investigation’ of possibility of producing ‘Alkali Pozzolan Cement (APC), that can be stored in a dry non-reacting form in air-tight bags. First it gives an overview of the use of Pozzolanic materials as supplementary / alternative cementitious materials in preparation of mortar and concrete. Then it presents the initial experimental results that lead to conceptualisation of APC. By mixing different proportions of quicklime and fly ash a number of APC mixtures were obtained. Using these mixtures mortar samples were prepared and their compressive strengths were tested. The initial findings were as expected that chemical activators and small quantity of OPC would be required as additional admixtures of APC, to activate the hydration process and to improve early strength. Based on the chemical composition of fly ash available in Western Australia, this study proposes the proportion of fly ash and quicklime to be mixed and the quantity of activating chemicals and OPC to be added. Finally it proposes a comprehensive experimental programme to confirm the conceptualisation of APC. That is to experimentally confirm the possibility of producing ‘APC for sustainable future.